Gli activation by the estrogen receptor in breast cancer cells: Regulation of cancer cell growth by Gli3. (15th February 2021) - Massah, Shabnam; Foo, Jane; Li, Na; Truong, Sarah; Nouri, Mannan; Xie, Lishi; Prins, Gail S.; Buttyan, Ralph
Abstract: Background: Gli is an oncogenic transcription factor family thought to be involved in breast cancer (BrCa) cell growth. Gli activity is regulated by a post-translational proteolytic process that is suppressed by Hedgehog signaling. In prostate cancer cells, however, Gli activation is mediated by an interaction of active androgen receptor proteins with Gli3 that stabilizes Gli3 in its un-proteolyzed form. Here we show that the estrogen receptor (ER), ERα, also binds Gli3 and activates Gli in BrCa cells. Moreover, we show that ER + BrCa cells are dependent on Gli3 for cancer cell growth. Methods: Transfection with Gli-luciferase reporter was used to report Gli activity in 293FT or BrCa cells (MCF7, T47D, MDA-MB-453) with or without steroid ligands. Co-immunoprecipitation and proximity ligation were used to show association of Gli3 with ERα. Gli3 stability was determined by western blots of BrCa cell extracts. ERα knockdown or destabilization (by fulvestrant) was used to assess how loss of ERα affects estradiol-induced Gli reporter activity, formation of intranuclear ERα-Gli3 complexes and Gli3 stability. Expression of Gli1 and/or other endogenous Gli-target genes in BrCa cells were measured by qPCR in the presence or absence of estradiol. Gli3 knockdown was assessed for effects on BrCa cell growth using the Cyquant assay. Results: ERα co-transfection increased Gli reporter activity in 293FT cells that was further increased by estradiol. Gli3 co-precipitated in ERα immunoprecipitates. Acute (2 h) estradiol increased Gli reporter activity and the formation of intranuclear ERα-Gli3 complexes in ER + BrCa cells but more chronic estradiol (48 h) reduced ERα-Gli complexes commensurate with reduced ERα levels. Gli3 stability and endogenous activity was only increased by more chronic estradiol treatment. Fulvestrant or ERα knockdown suppressed E2-induction of Gli activity, intranuclear ERα-Gli3 complexes and stabilization of Gli3. Gli3 knockdown significantly reduced the growth of BrCa cells. Conclusions: ERα interacts with Gli3 in BrCa cells and estradiol treatment leads to Gli3 stabilization and increased expression of Gli-target genes. Furthermore, we found tthat Gli3 is necessary for BrCa cell growth. These results support the idea that the ERα-Gli interaction and Gli3 may be novel targets for effective control of BrCa growth. Highlights: ERα, like AR, interacts with Gli3 and estradiol treatment increased ERα-Gli3 complexes. Estradiol treatment stabilized Gli3 and increased Gli transcriptional activity. Fulvestrant or ERα knockdown decreased Gli3 stability and Gli activity in BrCa cells. Estradiol treatment increased expression of growth promoting Gli target genes. Gli3 was needed for breast cancer cell growth.